Bridging Yoga and Mahāyoga: Samaya in Early Tantric Buddhism - Dalton, Jacob P. (Dynamics in the history of religions, 2022)
This chapter highlights the role of samaya in the early development of Tantric Buddhist ritual. In early tantric writings, samaya functions not only as a vow, or set of vows, to be observed, but as the Buddhas’ jñāna that was ritually installed within the heart of the practitioner. The paper shows how samaya was thereby central to both the initiation ceremony and the post-initiatory sādhana practices of the Yogatantra system of the Sarvatathāgatatattvasaṃgraha. In both of these ritual contexts, the entry of the samaya into the practitioner’s heart represented a key moment. Turning to the slightly later ritual traditions of early Mahāyoga, the chapter argues that the sexualisation of the earlier concept of samaya produced the secret initiation (Skt. guhyābhiṣeka) and the subsequent self-administering of the sacramental drop of bodhicitta that marked the culmination of sexual yoga, each paralleling the Sarvatathāgatatattvasaṃgraha’s initiation and self-consecration (Skt. svādhiṣṭhāna), respectively. The developmental continuities between Yoga and Mahāyoga are evident in certain early Mahāyoga works where the drop of bodhicitta is referred to as the supreme samaya (Tib. dam tshig mchog).